Solution for What is 67 percent of 73:

67 percent *73 =

(67:100)*73 =

(67*73):100 =

4891:100 = 48.91

Now we have: 67 percent of 73 = 48.91

Question: What is 67 percent of 73?

Percentage solution with steps:

Step 1: Our output value is 73.

Step 2: We represent the unknown value with {x}.

Step 3: From step 1 above,{73}={100\%}.

Step 4: Similarly, {x}={67\%}.

Step 5: This results in a pair of simple equations:

{73}={100\%}(1).

{x}={67\%}(2).

Step 6: By dividing equation 1 by equation 2 and noting that both the RHS (right hand side) of both
equations have the same unit (%); we have

\frac{73}{x}=\frac{100\%}{67\%}

Step 7: Again, the reciprocal of both sides gives

\frac{x}{73}=\frac{67}{100}

\Rightarrow{x} = {48.91}

Therefore, {67\%} of {73} is {48.91}

Solution for What is 73 percent of 67:

73 percent *67 =

(73:100)*67 =

(73*67):100 =

4891:100 = 48.91

Now we have: 73 percent of 67 = 48.91

Question: What is 73 percent of 67?

Percentage solution with steps:

Step 1: Our output value is 67.

Step 2: We represent the unknown value with {x}.

Step 3: From step 1 above,{67}={100\%}.

Step 4: Similarly, {x}={73\%}.

Step 5: This results in a pair of simple equations:

{67}={100\%}(1).

{x}={73\%}(2).

Step 6: By dividing equation 1 by equation 2 and noting that both the RHS (right hand side) of both
equations have the same unit (%); we have

\frac{67}{x}=\frac{100\%}{73\%}

Step 7: Again, the reciprocal of both sides gives

\frac{x}{67}=\frac{73}{100}

\Rightarrow{x} = {48.91}

Therefore, {73\%} of {67} is {48.91}